Hybrid nanogenerator-based self-powered double-authentication microsystem for smart identification. (August 2021) - Wen, Dan-Liang; Huang, Peng; Qian, Heng-Yi; Ba, Yan-Yuan; Ren, Zhen-Yu; Tu, Cheng; Gong, Tian-Xun; Huang, Wen; Zhang, Xiao-Sheng
Abstract: As an essential part of the Internet of Things (IoT), the identification technology is expected to meet higher requirements in terms of safety and durability due to the rapid development of the IoT, and signal recognition-based smart identification technologies that are highly secure, reliable, and even self-powered have attracted considerable attention in recent years. Herein, we present a self-powered double-authentication microsystem (DAM) composed of a piezoelectric-based active code and a triboelectric-based self-driven code to realize a high-security, high-identification-rate, and self-powered smart identification system. Polyvinylidene fluoride (PVDF) films with different lengths were arranged in binary sequence to construct the piezoelectric-based active code. A complementary filler and an opaque cover were implemented to conceal the coded information. The high consistency of output amplitudes of length-consistent piezoelectric units, the great difference of output amplitudes of length-inconsistent piezoelectric units, and the ultra-small speed dependence were experimentally confirmed, which enable the piezoelectric-based active code to achieve a high identification accuracy rate. The triboelectric-based self-driven code was implemented by a relative-sliding mode triboelectric nanogenerator (RS-TENG) to drive an information storage unit, such as a pre-compiled liquid crystal display (LCD). The obtained electrical energy during one operation could drive the LCD for 26 s, which allows the operator to have enough time to read the information. In addition, as attractive application prototypes, the two coded information were combined to realize personal identification and automatic unlocking. The high safety and identification accuracy rate make the self-powered DAM have attractive feasibility for applications in smart identification field. Graphical Abstract: ga1 Highlights: A self-powered double-authentication microsystem made of a piezo-active code and a tribo-self-driven code is proposed. High identification accuracy rate of the piezo-active code is experimentally confirmed. The harvested energy by a relative-sliding mode triboelectric nanogenerator (RS-TENG) can drive an LCD to work for 26 s. As attractive applications, personal identification and automatic unlocking are realized by using the proposed microsystem.